Hegemony in Discourse: How Armenia’s Security Dependence on Russia is Constructed and Reinforced - Daehli,Amanda (2025)
This thesis investigates how Armenia’s security dependence on Russia is discursively constructed and maintained through political texts. Analyzing the 1994 and 2020 ceasefire agreements ending the first and second Karabakh war, alongside 18 official statements from the Russian Ministry of Foreign Affairs (2020–2025), the study argues that these texts function not only as records of geopolitical events, but as instruments of hegemony—naturalizing asymmetric power relations and shaping Armenia’s perceived security needs. Drawing on Antonio Gramsci’s theory of hegemony, the analysis applies Critical Discourse Analysis (CDA) to key concepts such as common sense, war of position, coercion and conformism, ideology and historical bloc. A complementary geopolitical framework encompassing spatial, identity-based, and critical geopolitics—situates these discourses within the broader post-Soviet context. This research addresses a gap in the literature by examining the discursive strategies that legitimize Armenia’s dependency, strategies often overlooked in favor of material or institutional analyses. As Armenia seeks greater strategic autonomy, it remains constrained by entrenched narratives and inherited alliances. The chosen methodology highlights how ideological structures are embedded in language and how these discourses stabilize dependency over time. The findings reveal a shift in Russia’s coercion of Armenia—from the overt pressure evident in the 1994 ceasefire agreement to a more normalized and internalized dependence by the 2020 ceasefire agreement. By this point, Armenia’s reliance on Russia was no longer framed as a product of external force, but rather as a natural, self-evident necessity—what Gramsci terms “common sense”, a hegemonic narrative that renders power relations appear legitimate and unchangeable. Post-2020 developments reflect the early stages of a Gramscian “war of position”, in which emerging counternarratives begin to contest Russia’s dominant discourse yet remain largely shaped by its ideological boundaries. Russian rhetoric presents Armenia not merely as a strategic partner, but as an extension of Russia’s own national identity—reinforcing a historical bloc grounded in shared civilizational narratives. This framing delegitimizes Western alignment by portraying it as unnatural and destabilizing. Consequently, Armenia’s dependency on Russia emerges not only as a geopolitical reality, but as a hegemonically stabilized discourse, ideologically justified and symbolically sustained.